A arte educação na inclusão de crianças com Autismo na Escola Regular: o estado da arte - BARROS, Roseli Nunes (2024)
This study presents data from a bibliographical survey with a qualitative approach, carried out using the State of the Art in 2023. The aim was to investigate the discussions and scientific research on Art Education for the inclusion of children with Autism Spectrum Disorder (ASD), in the context of the regular school, in basic education. The searches for theoretical productions were carried out between April 4 and May 1, 2023 on the websites Google Scholar, Scielo, Capes Theses and Dissertations Database, UFPA Virtual and Physical Library Database, Altamira Campus, using the descriptors "art education and autism", "art education and inclusion", "art education and disability". In order to be included in the corpus, the object of investigation had to be related to Art Education aimed at the Autism Spectrum Disorder (ASD) audience, with a focus on primary school children, correspond to pedagogical proposals and have been published between 2008 and 2023. Fifty-four papers were found, of which 15 met the inclusion criteria and made up the corpus of this study. The research revealed a determining factor for the inclusion of students with disabilities and autism in the school context, such as the emphasis on continuing training for art teachers.